2017
DOI: 10.1038/s41598-017-02421-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the diagnostic value of different biomarkers in relation to various stages of diabetic nephropathy in type 2 diabetic patients

Abstract: Albuminuria is widely used to indicate early phases of diabetic nephropathy although it is limited by the fact that structural damage might precede albumin excretion. This necessitates identifying better biomarkers that diagnose or predict diabetic nephropathy. This is a cross-sectional hospital based study recruiting type 2 diabetic patients cohort aged 35–75 years with diabetes duration of ≥10 years. Out of total eligible 467 patients, 200 patients were with normal albumin excretion, 184 patients with microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 30 publications
9
61
0
Order By: Relevance
“…Therefore, RBP is a useful biomarker for tracking proximal tubular dysfunction in early DKD. 28,33,34 In this study, non-parametric tests showed that urinary UACR and TRF (glomerular injury markers) were higher and urinary THP (tubular damage marker) was lower in T2DM patients with hypothyroidism compared with other groups. Both urinary IgG and RBP levels were increased in the hypothyroidism group, but no significant differences in urinary IgG and RBP were observed among different thyroid function groups.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Therefore, RBP is a useful biomarker for tracking proximal tubular dysfunction in early DKD. 28,33,34 In this study, non-parametric tests showed that urinary UACR and TRF (glomerular injury markers) were higher and urinary THP (tubular damage marker) was lower in T2DM patients with hypothyroidism compared with other groups. Both urinary IgG and RBP levels were increased in the hypothyroidism group, but no significant differences in urinary IgG and RBP were observed among different thyroid function groups.…”
Section: Discussionmentioning
confidence: 55%
“…RBP is a carrier protein with low molecular weight (21 kDa) that binds to retinol and can be freely filtered through the glomerular barrier and almost completely reabsorbed in the proximal tubule. Therefore, RBP is a useful biomarker for tracking proximal tubular dysfunction in early DKD . In this study, non‐parametric tests showed that urinary UACR and TRF (glomerular injury markers) were higher and urinary THP (tubular damage marker) was lower in T2DM patients with hypothyroidism compared with other groups.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Other tests included in the yearly T2D evaluation are the lipid profile, liver tests, vitamin B12 in metformin treated patients, serum potassium in patients treated with ACE inhibitors, angiotensin receptor II blockers and diuretics [26]. It is foreseen that one or several more subtle parameters for glomerular filtration (urine transferrin, fibronectin, laminin, ceruloplasmin), podocyte injury (nephrin, podocalyxin, podocin), glomerulo-endothelial injury (glycoaminoglycan), tubular reabsorption, (cubilin, megalin, β2microglobulin, α1 microglobulin, retinol binding protein, cystatin C), tubular integrity (urine alkaline phosphatase, N-acetylglucosaminidase, alanin aminopeptidase, kidney injury molecule, type IV and type I collagen, matrix metalloproteinase 9), inflammation (PGE2 or PGF2α, TNFα, Interleukin 6, resistin, interleukin 1α, MCP-1 among others), oxidative stress (8-oxo-7,8-dihydro-2-deoxyguanosine), growth factors (transforming growth factor β1, vascular endothelial growth factor A, connective tissue growth factor) [24,28,29,30] will replace the current screening tests, as they are able to detect the kidney disease in earlier stages. Transferrin excretion is another candidate, as it was proven to proceed albuminuria in a larger cohort [31].…”
Section: Clinical Monitoring Of Type 2 Diabetes Patients With Chronicmentioning
confidence: 99%